Pobreza intergeracional no complexo de favelas do São João – Rio de Janeiro – Brasil - Motta, Astrid Maciel; Parente, Cristina Clara Ribeiro (Ámbitos. Revista Internacional de Comunicación, 2019)
This paper discusses a multidimensional approach to poverty, highlighting variables that allow us to gauge and interpret the reproduction of intergenerational poverty (Bird, 2007). This exploratory and descriptive research privileged a qualitative methodology based on semi - structured interviews conducted with 29 residents of the São João favelas complex, in Engenho Novo, Rio de Janeiro. We adopted a standard of comparative analysis between three generations: first generation are the progenitors (G1); the second, the generation under analysis (G2); and their descendants are (G3); the analysis was based on a systematic reasoning of comparison of 23 variables to create composite classification indices of the families. The study pointed out that the difficulties faced by residents of the favelas of Rio de Janeiro trigger mechanisms that produce and transmit poverty, and that family members, even though they had access to education and some public policy measures, remained largely in poverty, given the social dynamics experienced in the context of the favela. The factors promoting the intergenerational poverty cycle in these territories are present in the intra-and extra familial dimension, as referred to by Bird (2007). In this way, we conclude that the effectiveness of public policies aimed at the disruption of poverty require in-depth studies on the social dynamics specific to the context of the Rio de Janeiro favelas to subsidize the formulation of measures consubstantiated in the particularities of the place.